Geological nonhomogeneity of soils - Kaczyński, R.; Bąkowska, A. (Інститут прикладних проблем механіки і математики ім. Я.С. Підстригача НАН України, 2008)
The nonhomogeneity of typical soils in Poland (Tertiary, Miocene and Pliocene clays, Quaternary glacial tills and loesses, Holocene fluvial sands) was analyzed in the paper. The analysis was limited to the presentation of the results of investigation of variability coefficient V and Kagan nonhomogeneity coefficient K1 determined for the basic parameters of lithological, microstructural, physical and mechanical properties used for designing the foundations of engineering objects. Nonhomogeneity of soils is determined by the geological conditions of their origin as well as by later changes. Проаналізовано неоднорідність типових ґрунтів на території Польщі. Аналіз обмежено до подання результатів дослідження зміни V, а також параметра змінності K1, визначених для основних літологічних мікроструктурних параметрів, і фізичних та механічних параметрів, які використовуються при проектуванні об’єктів. Неоднорідність ґрунтів зумовлена геологічними умовами, а також наступними змінами. Проанализирована неоднородность типовых почв на территории Польши. Анализ ограничен представлением результатов исследования изменения V, а также параметра K1, определяемых для основных литологических микроструктурных параметров, физических и механических свойств, используемых при проектировании объектов. Неоднородность почв обусловлена геологическими условиями, а также последующими изменениями.